Kesehatan Fisik dan Mental Remaja: Hubungan Status Gizi dan Tingkat Stres Di Sekolah Menengah Kejuruan - Anggriany, Nissa; Fajriani, Laksmi Nur; Sukanty, Ni Made Wiasty; Anisah, Anisah; Isasih, Widani Darma; Ardian, Junendri; Saputra, I Putu Bayu Agus (Bakti Sekawan : Jurnal Pengabdian Masyarakat, 2026)
Adolescents are an age group vulnerable to various health problems, both physical and mental, along with the biological and psychosocial changes that occur during their developmental phase. Nutritional status and stress levels are two important aspects that play a role in determining adolescent well-being, however existing evidence regarding the relationship between these two variables remains inconsistent. This community service activity aims to describe the nutritional status and stress levels of adolescents and analyze the relationship between nutritional status and stress levels in adolescents in the school environment. The activity was carried out at SMKN 2 Lembar involving 21 adolescents aged 15–17 years using an observational analytical approach with a cross-sectional design. Data collection was carried out by filling out questionnaires on respondent characteristics and stress levels, as well as anthropometric measurements to determine nutritional status. Data were analyzed univariately and bivariately using the Fisher Exact test as an alternative. The results showed that most respondents were 16 years old (42.8%), had good nutritional status (90.5%), and experienced moderate stress (90.5%). The results of the bivariate analysis showed no significant relationship between nutritional status and stress levels in adolescents (p = 0.890). The conclusions of this activity indicate that stress levels in adolescents are not directly related to nutritional status but are likely more influenced by psychosocial factors. Therefore, community service programs in schools need to be implemented holistically, integrating nutrition education and mental health promotion to improve adolescent well-being.